Innovación tecnológica del proceso de recaudación de ingresos y su incidencia en la atención a los usuarios del Gad Quevedo, 2023 - Quintana Mora, Ingrid Juliana (2025)
This research focuses on analyzing the incidence of technological innovation in the revenue collection process of the Decentralized Autonomous Government of Quevedo, which is located in the municipal citadel. The problem is that despite having digital platforms, they continue to be restricted because users’ resort to the in-person payment method. This is due to reasons such as distrust in digital platforms, poor handling of the platform and the perception that in-person procedures are safer. For them, the objective of analyzing the incidence of technological innovations to improve user service was raised, through data analysis and the application of survey, interview, and performance indicators, this study is justified, which is part of fundamental to promoting efficiency, effectiveness and transparency in revenue collection processes. This type of methodology has quantitative and qualitative approaches which was based on 380 surveys directed at users of the Decentralized Autonomous Government of Quevedo and interviews with the head of collection and the head of ICT. I conclude that despite the adoption of digital platforms by the Decentralized Autonomous Government of Quevedo, there are still users who prefer to use the in-person window due to lack of knowledge of the platform or because they feel safer making payments through the in-person window.